Transverse nasal groove. - Panasia, S.; Paradisi, M. (European Journal of Pediatric Dermatology, 2004)
Clinical features. The transverse nasal groove (TNG) is an embryonic line of junction -Fig. 2- (6). Along the latter erythema, hyperpigmentation (3), milia, cysts and comedos (4), sometimes inherited by an autosomal dominant trait (1) may occur. Clinical course. The linear lesions get evident in the first years of age and persist indefinitely, although significantly improving with years. Differential diagnosis. The erythematous linear lesions should be differentiated from the transverse folds of the subjects with allergic rhinitis (2, 5), due to the common habit (atopic greeting) of pulling up with one’s fingers the tip of the nose. The atopic sign consists of a few, small, transverse folds, which disappear when stretching down the tip of the nose, whereas TNG is unique and does not disappear when pulling down the tip of the nose.